2015
DOI: 10.1016/j.cell.2015.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Non-lethal Inhibition of Gut Microbial Trimethylamine Production for the Treatment of Atherosclerosis

Abstract: SUMMARY Trimethylamine N-oxide (TMAO), a gut microbiota dependent metabolite, both enhances atherosclerosis in animal models and is associated with cardiovascular risks in clinical studies. Here we investigate the impact of targeted inhibition of the first step in TMAO generation, commensal microbial trimethylamine (TMA) production, on diet-induced atherosclerosis. A structural analogue of choline, 3,3-dimethyl-1-butanol (DMB), is shown to non-lethally inhibit TMA formation from cultured microbes, to inhibit d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
871
3
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,066 publications
(912 citation statements)
references
References 35 publications
27
871
3
11
Order By: Relevance
“…The present study shows that elevated TMAO levels at time of MI is further associated with poor outcome. Moreover, a non-lethal choline analogue to inhibit bacterial production of trimethylamine, in turn reducing the levels of circulating TMAO [29], has been recently described, and intervention studies using this or similar compounds will be important to address the causative role of TMAO on coronary artery disease and outcomes in the future. In an initial investigation into TMAO kinetics post-acute MI in a small cohort, circulating TMAO levels were observed to rise and stabilize between day 1 and 5 post-admission.…”
Section: Discussionmentioning
confidence: 99%
“…The present study shows that elevated TMAO levels at time of MI is further associated with poor outcome. Moreover, a non-lethal choline analogue to inhibit bacterial production of trimethylamine, in turn reducing the levels of circulating TMAO [29], has been recently described, and intervention studies using this or similar compounds will be important to address the causative role of TMAO on coronary artery disease and outcomes in the future. In an initial investigation into TMAO kinetics post-acute MI in a small cohort, circulating TMAO levels were observed to rise and stabilize between day 1 and 5 post-admission.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis, described in detail below, has recently been supported by substantial evidence in animals and humans (Wang, et al, 2011;Koeth et al, 2013;Tang et. al., 2013;Jonsson and Bäckhed;Troseid, et al, 2015;Wang et al, 2015;Warrier, et al, 2015). Briefly, trimethylamine (TMA)-containing dietary compounds, found mainly in meat, milk, some fish, and other animal foods (e.g., lecithin, choline, betaine, carnitine) are converted by TMA lyases (lyases) in gut bacteria to TMA, which is absorbed and then oxidized by hepatic flavin mono-oxygenase 3 (FMO3) to the toxic trimethylamine N-oxide (TMAO).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent, study Wang et al [19] demonstrated that 3,3-dimethyl-1-butanol (DMB), a structural analog of choline, blocks the intestinal TMA formation through the inhibition of the microbial TMA lyase, and results in reduced TMAO levels. Thus, 'drugging the microbiome' with DMB may be a novel approach for the prevention/treatment of atherosclerosis (Figure 3).…”
Section: Atherosclerosis and Thrombosis Riskmentioning
confidence: 99%
“…Inhibition of intestinal microbial trimethylamine (TMA) synthesis by 3,3-dimethyl-1-butanol (DMB) and attenuation of atherosclerosis [19].…”
Section: Journal Of Healthcare Communications Issn 2472-1654mentioning
confidence: 99%